2016
DOI: 10.1016/j.toxicon.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Serine proteinases from Bothrops snake venom activates PI3K/Akt mediated angiogenesis

Abstract: The discovery of rapid acting and powerful angiogenic proteins are of significant interest in the treatment of various human disorders associated with insufficient angiogenesis such as ischemia, menorrhagia and delayed wound healing. Snake venoms consist of a mixture of bioactive proteins and polypeptides and are rich sources of pharmacologically important molecules. Serine proteinases are one of the abundant proteins present in Bothrops snake venoms and possess multiple biological functions including the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
0
16
1
3
Order By: Relevance
“…In the murine model, Peruvian B. brazili exhibited minimum hemorrhagic dose (MHD) of 7.40 μg/ mouse), minimum dermonecrotic dose (MND) of 152.15 μg/ mouse, minimum coagulant dose against plasma (MCD-P) and fibrinogen (MCD-F) of 19.20 and 1020.0 μg/mL, respectively, and minimum defibrinogenating dose (MDD) of 7.0 μg/mouse [11]. Although described as a new Bothrops from Brazil 65 years ago [15], very few studies have been reported on the toxin arsenal of the Brazil's lancehead venom, and these were mainly focused on the pharmacological effects and possible biotechnological applications of isolated toxins [21][22][23][24][25][26][27][28][29][30][31], including acidic and basic phospholipase A 2 (PLA 2 ) molecules (myotoxic Braziliase I and II, MTX I and II, brazilitoxins II and III) [23][24][25][26]; a PI-snake venom metaloproteinase (SVMP), with in vitro antiplasmodial properties [27]; coagulant thrombin-like and pro-angiogenic snake venom serine proteinase (SVSP) [28,29]; and a hyaluronidase [30].…”
Section: Introductionmentioning
confidence: 99%
“…In the murine model, Peruvian B. brazili exhibited minimum hemorrhagic dose (MHD) of 7.40 μg/ mouse), minimum dermonecrotic dose (MND) of 152.15 μg/ mouse, minimum coagulant dose against plasma (MCD-P) and fibrinogen (MCD-F) of 19.20 and 1020.0 μg/mL, respectively, and minimum defibrinogenating dose (MDD) of 7.0 μg/mouse [11]. Although described as a new Bothrops from Brazil 65 years ago [15], very few studies have been reported on the toxin arsenal of the Brazil's lancehead venom, and these were mainly focused on the pharmacological effects and possible biotechnological applications of isolated toxins [21][22][23][24][25][26][27][28][29][30][31], including acidic and basic phospholipase A 2 (PLA 2 ) molecules (myotoxic Braziliase I and II, MTX I and II, brazilitoxins II and III) [23][24][25][26]; a PI-snake venom metaloproteinase (SVMP), with in vitro antiplasmodial properties [27]; coagulant thrombin-like and pro-angiogenic snake venom serine proteinase (SVSP) [28,29]; and a hyaluronidase [30].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless the stimulatory or inhibitory effect, these mediators certainly play a role in mediating the pro-and anti-angiogenic balance, and investigating them is crucial to provide new alternatives for public health issues such as the application of bioengineering tools therapeutic strategies which success depends on angiogenesis, including tissue/organ transplantations and the treatment of diseases associated with impaired vascular irrigation (Liu et al, 2017;Said and Geoffrey, 2013;Mimura et al, 2016). Studies in this field have pointed the anti-inflammatory protein annexin A1 (AnxA1), as well as the serine protease isolated from Bothrops atrox venom (BaSp) as potent inductors of neovascularization (Bhat et al, 2016;M Yi and Schnitzer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, possuem também resíduos de cisteína, que são responsáveis pela formação das pontes dissulfeto. Apesar de serem glicoproteínas de cadeia única, interagem com uma grande diversidade de substratos, e possuem uma massa molecular que varia entre 26 e 67 kDa (MAMEDE, 2015;AMORIM et al, 2018).…”
Section: Serinoproteasesunclassified
“…As serinoproteases são sintetizadas como zimogênios e desempenham um papel importante na atividade patofisiológica induzida pela peçonha, pelo fato de estarem envolvidas em desordens hemostáticas, como ter influência na agregação plaquetária, no sistema fibrinolítico, na pressão sanguínea, além de poderem modular a angiogênese (AMORIM et al, 2018;COSTA et al, 2018). Ainda apresentam ação anticoagulante, pois podem ou realizar a degradação proteolítica de componentes do sistema hemostático, ou ativar e inibir de forma específica fatores da coagulação e fibrinólise.…”
Section: Serinoproteasesunclassified
See 1 more Smart Citation